Antibiotics Knowledge and Prescription Patterns Among Dental Practitioners in Croatia, Bosnia and Herzegovina, and Serbia: A Comparative E-Survey with a Focus on Medically Healthy and Compromised Patients - Marija Badrov; Danijela Marovic; Antonija Tadin (MDPI AG, 2024)
Background: The non-specific prescription of antibiotics, especially in dentistry, contributes to the global problem of antimicrobial resistance and highlights the need for education on the proper use and serious consequences of overprescribing these drugs. The main objective of this study is to assess and evaluate antibiotic knowledge and prescribing patterns in dental practice in Croatia, Bosnia and Herzegovina, and Serbia, focusing on understanding the rationale for prescribing, adherence to evidence-based guidelines, and dentists' awareness of antibiotic resistance. Methods: A total of 795 dentists participated in this electronic cross-sectional survey (Croatia N = 336, Bosnia and Herzegovina N = 176, and Serbia N = 283). The study utilized a self-structured questionnaire to collect data on various aspects of antibiotic use, including knowledge, prescribing practices, awareness of guidelines, and demographic and professional information about dentists. Data analysis included the Mann-Whitney test, the Kruskal-Wallis test with post hoc analysis, and chi-square tests, with statistical significance set at p < 0.05. Results: The overall score for the participants' knowledge of antibiotics was 6.40 ± 1.40 out of a maximum of eight points, which indicates a generally good level of knowledge among dentists. Factors such as gender, specialty, and practice location significantly influenced the level of knowledge (p < 0.05). However, actual prescribing practice was a cause for concern. Only 66.1% of Croatian dentists felt they had received adequate training during their studies, and even fewer in Serbia (48.4%) and Bosnia (46.6%). It is noteworthy that 9.7% of dentists in Bosnia and Herzegovina prescribe antibiotics at the request of patients, while 22.3% of Croatian and 25.4% of Serbian dentists do so. Many dentists prescribe no or only one antibiotic per week. In addition, 50.9% of Croatian dentists reported adverse effects related to the use of antibiotics, while only 31.3% of Bosnian and 33.6% of Serbian dentists reported similar experiences. Conclusions: While the study results indicate that dentists in the region generally possess good knowledge of antibiotic use, there are significant discrepancies between this knowledge and actual prescribing practices. This highlights the need for enhanced educational programs and awareness initiatives focused on proper antibiotic guidelines to improve prescribing behaviors.